Grey Area Antara Tindak Pidana Korupsi dengan Tindak Pidana Perbankan - Ifrani Ifrani (Jurnal Konstitusi, 2016)
Nowadays, in Indonesia, there are so many laws appear after KUHP which regulate about criminal laws, beside providing the rules of material criminal law againts to KUHP, also providing the formal rules which againts to KUHAP (formal criminal laws). In criminal laws that related to financial government, has common law which is regulated by laws itself. And corruption criminal laws which has the regime of law itself, but it is still unclear where could be qualificated as crimnal laws in financial government and which could be qualificated as corruption criminal laws. It is still in the “grey area”